2018
DOI: 10.1038/s41598-018-27166-x
|View full text |Cite
|
Sign up to set email alerts
|

Optical dispersion control in surfactant-free DNA thin films by vitamin B2 doping

Abstract: A new route to systematically control the optical dispersion properties of surfactant-free deoxyribonucleic acid (DNA) thin solid films was developed by doping them with vitamin B2, also known as riboflavin. Surfactant-free DNA solid films of high optical quality were successfully deposited on various types of substrates by spin coating of aqueous solutions without additional chemical processes, with thicknesses ranging from 18 to 100 nm. Optical properties of the DNA films were investigated by measuring UV-vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 43 publications
(55 reference statements)
0
16
0
Order By: Relevance
“…Therefore, it is highly desirable to maintain the full biocompatibility of DNA by removing the lipid complex to use aqueous solution precursors in the refractive index control of DNA-TSFs. The authors have proposed adding vitamin B2 to lipid-free DNA-TSFs to achieve efficient refractive index control [12].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is highly desirable to maintain the full biocompatibility of DNA by removing the lipid complex to use aqueous solution precursors in the refractive index control of DNA-TSFs. The authors have proposed adding vitamin B2 to lipid-free DNA-TSFs to achieve efficient refractive index control [12].…”
Section: Introductionmentioning
confidence: 99%
“…With a similar approach, we could previously identify molecular related UV-Vis absorptions by the analysis of difference SE spectra of biomolecular SAMs [ 49 , 54 ]. Recent papers focused on the optical properties of DNA thin solid films [ 55 , 56 , 57 ], but to the best of our knowledge, this is the first experimental observation in SE difference spectra of molecular absorption on DNA monolayers chemisorbed on gold.…”
Section: Resultsmentioning
confidence: 99%
“…Previous authors have demonstrated the ability of DNA to improve LED performance [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ] and as a component in the fabrication of photovoltaics [ 14 , 15 , 16 , 17 ]. Moreover, DNA films can be used as a matrix and doped with functional materials that can alter the optical and electronic properties of the thin film, which may be useful for different types of organic devices [ 18 , 19 , 20 ]. Due to the discovery of these promising physical properties, DNA thin-film devices have become a notable research interest in materials science.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, research has focused on controlling the electronic and optical properties of surfactant-modified thin films, and applications have relied on characterizing results from DNA–CTMA complexes. Recently, groups have been making progress towards efficient surfactant-free thin films because the toxicity of CTMA makes DNA–CTMA solutions ineligible for many biological applications and becomes insoluble in water [ 14 , 19 , 26 ]. However, research on surfactant-free thin DNA films has focused on how to affect the physical properties of the films, such as optical dispersion and refractive indices [ 19 , 25 , 27 , 28 , 29 , 30 ] and not on improving the efficiency of thin-film fabrication or standardizing the production of films with tunable thickness within a controlled range of uniformity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation